Effectiveness factors and impacts on policymaking of science-policy interfaces in the environmental sustainability context. Issue 140 (February 2023) - Wagner, Niklas; Velander, Sara; Biber-Freudenberger, Lisa; Dietz, Thomas
Abstract: Organizations connecting science and policy, referred to as science-policy interfaces, aim to support policymakers with decision-relevant knowledge, scientific findings, and co-production processes. Given the rising significance of the role of evidence in decision-making in a world dealing with complex problems, a proliferation of literature has developed theories on the effectiveness of such interfaces. While there are studies providing evidence of these interfaces influencing policy, there is limited understanding of the comprehensive range of impacts on policies among multiple science-policy interfaces. Through a systematic review we analyzed how 69 research articles investigated structured science-policy interfaces related to environmental sustainability, organizing their types, effectiveness factors, outputs and related impacts on policymaking. We found a majority of the studies focused on global expert groups generating assessments leading to policy formulation and agenda setting, driven by social learning among policymakers. Most references regarding factors enabling impacts on policymaking of science-policy interfaces were found with regards to stakeholder participation, diverse background of experts, interdisciplinarity, and the communication of complexity. Further research is needed to explore the 'fuzzy boundary' between science and policy among different types and models of science-policy interfaces, the interdependencies between effectiveness factors, and the exogenous forces influencing the relationship between Science-Policy-Interfaces outputs and impacts on policymaking. By synthesizing the impacts on policymaking and associated factors of science-policy interfaces found in the literature, our review harmonizes the observations made by scholars on the effectiveness of SPIs in impacting sustainable development policies. Highlights: Science-policy interfaces enhance connectivity between experts and policymakers. There is limited literature synthesizing policy impacts of multiple SPIs so far. We synthesize 69 studies on SPIs finding a focus on global expert groups. The key SPI output are assessments contributing to social learning of policymakers. Most SPI cases referred to effectiveness factors of credibility and legitimacy.